Intern
Joined: 18 Jul 2007
Posts: 15
Followers: 0
Kudos [?]:
4
[0], given: 0

(S1) (xy)/x > 0 can be rewritten as x/x  y/x > 0 =
1  y/x > 0 = [1 > y/x]
x = 4, y = 3 will satisfy, however just try the opposite, x = 4, y = 3 will also satisfy
INSUFF
(S2) (x^2  y^2)/x^2 > 0 can be rewritten in the same fashion as above to [1 > (y^2)/(x^2)]
try plugging in the same values as above, both work
INSUFF
(S1 & S2) because we used the same test values for both equations, we don't even have to check.
we know that x=4, y=3 will satisfy both equations as well as x=4,y=3
so E
